Pengembangan Media Box Mengenal Bilangan dan Operasinya Bagi Siswa Kelas 1 Di SDN Gadang 1 Kota Malang - Martini Dwi Purnama; Edy Bambang Irawan; Cholis Sadijah (FMIPA UNIVERSITAS NEGERI MALANG, 2017)
Learning mathematics in grade 1 using pieces of instructional media will generate motivation, stimulating learning activities, abstract concept and bring the psychological effects of a child. This study aims to generate media box material to know numbers and operations are valid, practical, effective and attractive. The model of development used modification 4D model developed by Thiagarajan. Validation results declared invalid by subject matter experts and very valid by media experts. Practicality and attractiveness of the product reaches 94 % categorized as very practical and very attractive. While the effectiveness of a product is marked with the positive response of students who achieve mastery of at least about 82 %